Advances in Molecular Mechanisms and Immunotherapy Involving the Immune Cell-Promoted Epithelial-to-Mesenchymal Transition in Lung Cancer. (19th August 2019) - De Matteis, Serena; Canale, Matteo; Verlicchi, Alberto; Bronte, Giuseppe; Delmonte, Angelo; Crinò, Lucio; Martinelli, Giovanni; Ulivi, Paola
Abstract : Immunotherapy has offered a new opportunity for the treatment of many malignancies. In patients with lung cancer, immune checkpoint inhibitors have significantly improved survival. However, little is known about predictive factors or primary and acquired resistance mechanisms. Epithelial-to-mesenchymal transition (EMT) is a complex of phenotypic changes involved in carcinogenesis and resistance to cancer treatments. Specifically, immune cells in the tumor microenvironment can promote EMT, and mesenchymal phenotype acquisition negatively regulates the anticancer immune response. EMT is associated with higher expression of PD-L1 and other immune checkpoints. In this review, we focused on the role of EMT in the interplay between tumor cells and the immune system, with particular emphasis on lung cancer. On the basis of our findings, we hypothesize that the effects of EMT on immune cells could be overcome in this disease by a new combination of immune checkpoint inhibitors.